Street-level corruption: fatores institucionais e políticos da corrupção burocrática - Spinelli, Mário Vinícius Claussen (2016)
This study investigates institutional and political factors that determine corruption practiced by street-level bureaucrats, according to the classic concept proposed by Michael Lipsky. It sought subsidies for the establishment of a new concept related to the phenomenon: street-level corruption. Based on the literature about corruption published after the end of the 1980s - in which the approach for determining the causes of the phenomenon was changed, focusing on aspects related to the economic interests of the stakeholders - this study analyzes what institutional factors were determinants for its occurrence. The study also examined whether political conditions had contributed or not, first for the fraud and after to its own detection. From the case study of the corruption scandal known in Brazil as the 'Mafia of Tax ISS-Occupancy Permit in the city of São Paulo,” it was observed that the fraud was largely determined by institutional and political factors. In this sense, the research has shown that the power conferred to agents, combined with spaces of discretion present in their activity and deficits of accountability mechanisms were crucial to the practice of street-level corruption. In addition, the study concluded that political factors have contributed to the occurrence of the scandal, as its own discovery by the Municipal Administration. The results of this study are important to conclude that corruption, at least when it is practiced by street-level bureaucrats, is largely related to institutional and political factors. This diagnosis can also be useful for better understanding of the phenomenon and for designing effective strategies for combating corruption.